Employment Deconcentration in European Metropolitan Areas - Eran Razin, Martin Dijst, Carmen Vazquez (Springer, 2007)
European metropolitan areas have experienced a marked reorganization associated with the processes of globalization and the European integration of economic activities on various spatial scales. Much of this change is particularly evident at the edge of central cities, further away at suburban locations and on the fringes of expanding metropolitan areas. These spatial processes of urban expansion, sprawling development, and employment deconcentration present constant challenges to urban quality of life, raising concerns about excessive consumption of land and energy, traffic congestion, and so forth. These concerns prompt the formulation of public policies at various levels of government: European Union agencies, national, and sub national public authorities. The challenges posed by the spatial reorganization of economic activities within European metropolitan areas and their implications for the quality of life inspired the research project sponsored by the European Commission 5th Framework, entitled: Spatial Deconcentration of Economic Land Use and Quality of Life in European Metropolitan Areas (SELMA). The primary goal of SELMA was to design urban planning and management strategies to ensure the maintenance of the quality of life in European metropolitan areas. To this end, three broad activities were defined. The first focused on the identification and analysis of the driving forces and dynamics behind the process of economic land-use deconcentration in metropolitan areas. An analysis of the impacts of these processes on urban quality of life formed the heart of the second activity. Finally, the effectiveness of the public policy response to the challenges of economic land-use deconcentration in various governance systems was assessed. These activities were carried out in 14 metropolitan areas in seven countries: Denmark, the United Kingdom, the Netherlands, the Czech Republic, Spain, Italy, and Israel. This book presents the results of part of the SELMA endeavour, focusing mainly on the development trends over a 10-year period relating to the form and magnitude of employment dispersal and the role of public policies in creating the present processes. The main objective was to provide the infrastructural knowledge base relating to European urban trends and to provide rich comparative case-study evidence. In the scientific literature, the broad phenomenon of urban sprawl has been discussed widely. However, most studies have featured patterns, processes, and policy debates in the United States and concentrated mainly on residential spatial reconfigurations. The few studies of the deconcentration of economic land uses are limited in scope and in most cases lack a cross-national comparative perspective. Such a perspective can contribute substantially to the explanation of the patterns and processes of deconcentration, in particular to the assessment of the impact of different governance systems and public policies on deconcentration. In this book we discuss the scale and form of economic deconcentration and qualityof- life implications within selected metropolitan areas, referring to attributes of governance systems, thus aiming to provide useful insights for possible changes in metropolitan governance and policies.